Trinucleating bipyridyl ligands; Synthesis and structure of cobalt-benzoquinone complex of cyclotriphosphazenes bearing dioxybipyridine groups - Jung, OS; Kim, YT; Lee, YA; Kim, YJ; Chae, HK (AMER CHEMICAL SOC, 1999)
Exocyclic tris(bidentate) ligands attached to a cyclo-triphosphazene skeleton have been prepared and characterized. The cobalt complexes of the ligand have an unusual structure and demonstrate Co-III/Co-II equilibrium over a wide temperature range.
Keywords: ELECTRON-TRANSFER; REDOX ISOMERISM; MONONUCLEAR; BISTABILITY; SEMIQUINONE; CATECHOLATE; BEHAVIOR; SERIES; RING